STRATEGI MEDIA RELATIONS ALLIANZ INDONESIA DALAM MEMPEROLEH BERITA POSITIF - Farah Adila; Yustikasari Yustikasari; Renata Anisa (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the stages of managing relationships, developing strategies and developing networks in Allianz Indonesia's media relations strategy. Through the Corporate Communications department, Allianz Indonesia pays attention and carries out media relations activities as a way to get positive news that can affect the company's image and reputation. This research use descriptive method with qualitative data presentation. The results showed that in the stage of managing relationships, Allianz Indonesia has built intensive communication with media partners, either directly or indirectly. Also, compiling the media list according to the type of audience, coverage and level of the mass media. Furthermore, Allianz Indonesia's public relations practitioners have a media relations team that acts as writer, spokesperson and media coordinator. At the strategy development stage, the company's goals have been set to increase awareness, change attitudes and encourage public action, by carrying out various media activities such as Press conferences, media gatherings, media workshops, journalist competitions, and others. The Corporate Communications Department has also conducted a SWOT analysis. At the stage of developing the network, Allianz Indonesia has joined two associations, namely the Indonesian General Insurance Association (AAUI) and the Indonesian Life Insurance Association (AAJI)